2011
DOI: 10.1590/s0006-87052011000400021
|View full text |Cite
|
Sign up to set email alerts
|

Influência do parasitismo pelo nematoide de galhas nos níveis de nutrientes em folhas e na fenologia de goiabeira 'Paluma'

Abstract: A redução no vigor de goiabeiras parasitadas por Meloidogyne enterolobii é consequência das alterações ocorridas no sistema radicular que desencadeia uma síndrome caracterizada por desequilíbrio nutricional. Para caracterizar esse desequilíbrio, foram efetuadas análises químicas de folhas com três tipos de sintomas visuais (folhas sem sintoma, com sintoma leve e sintoma severo) de goiabeiras 'Paluma', em duas épocas: fevereiro e agosto. As plantas foram cultivadas com e sem inoculação de Meloidogyne enterolobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Because of the reduction in the volume of the root system, there was less absorption and transport of water and soil nutrients, which affected the development and growth of plants. Due to this chain of events, visual nutrient deficiency symptoms were observed in the leaves of araçá species susceptible to M. enterolobii, mainly for nitrogen, phosphorus, potassium and magnesium, which are similar to those described in guava trees (Almeida et al, 2011).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Because of the reduction in the volume of the root system, there was less absorption and transport of water and soil nutrients, which affected the development and growth of plants. Due to this chain of events, visual nutrient deficiency symptoms were observed in the leaves of araçá species susceptible to M. enterolobii, mainly for nitrogen, phosphorus, potassium and magnesium, which are similar to those described in guava trees (Almeida et al, 2011).…”
Section: Resultssupporting
confidence: 67%
“…enterolobii is the main limiting factor for guava cultivation and the typical symptoms of the disease are tanning, yellowing, and fall of leaves, leading to plant death (Carneiro et al, 2001). The infected roots present numerous galls, generalized necrosis, and few radicels, which aggravate the symptoms of nutritional deficiency (Almeida et al, 2011). In addition, infection by M. enterolobii in guava is generally associated with soil fungi (Gomes et al, 2013), which interact synergistically resulting in greater damage to crops, as reported for common bean (Phaseolus vulgaris) and passion fruit (Passiflora edulis f. flavicarpa) (Fischer et al, 2010;Al-Hazmi & Al-Nadary, 2015).…”
mentioning
confidence: 96%
“…Studies in guava [ 68 ], coffee [ 69 ], peach and almond [ 70 ] have shown that disease status of RKN infected trees is related to symptoms triggered by nutritional imbalances in the concentration of nitrogen, calcium, manganese and magnesium in several tissues in adult plants. Furthermore, because our binary phenotypic data fitted the same epistatic models proposed earlier [ 47 ], we further considered the hypothetical involvement of a second genetic locus interacting with the underlying genes on chromosome 3.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in guava [64], coffee [65], peach and almond [66] have shown that disease status of RKN infected trees is related to symptoms triggered by nutritional imbalances in the concentration of nitrogen, calcium, manganese and magnesium in several tissues in adult plants. Furthermore, because our binary phenotypic data fitted the same epistatic models proposed earlier [43], we further considered the hypothetical involvement of a second genetic locus interacting with the underlying genes on the chromosome 3.…”
Section: Enterolobii Resistance Might Be Triggered By Mineral Nutrien...mentioning
confidence: 99%